PENGARUH HAK PSIKOLOGIS DAN IKLIM KETERLIBATAN KARYAWAN TERHADAP PERILAKU KEWARGAAN ORGANISASI DENGAN MEDIASI KOMITMEN AFEKTIF ORGANISASI DI KECAMATAN KANDIS - Milka, Maya Novasari; Junaidi; N, Arizal (Jurnal Ilmiah Ekonomi Dan Bisnis, 2024)
The purpose of this study was to conceive a decision-making phenomenon exclusively according to the headman of the Kandis subdistrict and the unpleasant impact on village officials. The research method used was continuous study also collecting information for considerable analysis. This research was focused on four variables; psychological entitlement, employee involvement climate, organizational affective commitment, and organizational behavior citizenship. In this research, the number of village officials’ population in Kandis subdistrict was ninety-six. The result indicates that psychological entitlement and employee involvement climate have a significant positive impact significantly to organizational behavior citizenship. In comparison, organizational affective commitment has a negative impact significantly against organizational behavior citizenship. Furthermore, psychological entitlement was discovered to have a negative impact significantly as well against organizational behavior citizenship through organizational affective commitment, whereas employee involvement climate has a positive impact significantly on organizational behavior citizenship through organizational affective commitment. By using Structural Equation Modeling (SEM) analysis with SmartPLS support this research was conducted, and the data were collected through filling out the questionnaire by respondents. Keywords: Psychological Entitlement, Employee Involvement Climate, Organizational Affective Commitment, Organizational Behavior Citizenship